Adsorbents as antiendotoxin agents in experimental colitis. Issue 1 (January 1993) - Gardiner, K R; Anderson, N H; McCaigue, M D; Erwin, P J; Halliday, M I; Rowlands, B J
Abstract : The intestinal mucosa protects the body from a large reservoir of intraluminal pathogenic bacteria and endotoxins. This mucosal barrier is disrupted by the inflammation and ulceration of inflammatory bowel disease and may permit the absorption of toxic bacterial products. Systemic endotoxaemia has been demonstrated in ulcerative colitis and Crohn's disease and correlates with the extent and activity of disease. In this study the efficacy of absorbents as antiendotoxin agents in a hapten induced rat model of colitis is investigated. Induction of colitis was associated with systemic endotoxaemia. Enteral administration of terra fullonica and kaolin, but not of charcoal, significantly reduced systemic endotoxaemia (terra fullonica 4.2 (1.40) pg/ml; kaolin 5.29 (1.86) pg/ml; charcoal 32.7 (16.6) pg/ml; water 39.8 (12.6) pg/ml). Data expressed as mean (SE). With increasing severity of colitis, there was a decreasing ability of adsorbent therapy (terra fullonica) to control systemic endotoxaemia. Enteral administration of adsorbents controls gut derived systemic endotoxaemia in experimental colitis in animals and may be a useful antiendotoxin treatment in patients with inflammatory bowel disease.